1994
DOI: 10.1073/pnas.91.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Autographa californica nuclear polyhedrosis virus host range by interspecific replacement of a short DNA sequence in the p143 helicase gene.

Abstract: Recombinant baculoviruses obtained by coinfection ofinsect cells with Autographa californica and Bombyx mori nuclear polyhedrosis viruses (AcNPV and BmNPV, respectively) possess a wider in vitro host range than either parent virus. To localize the DNA sequences responsible for this species specificity, we used a two-step method of production and selection of recombinant viruses with altered specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 28 publications
1
74
0
1
Order By: Relevance
“…The p143 gene of AcMNPV has helicase activity (McDougal & Guarino, 2001) and has been implicated as a host-range factor (Croizier et al, 1994;Kamita & Maeda, 1997). For example, although AcMNPV and BmNPV share high DNA sequence similarity, AcMNPV could not replicate in B. mori cells and BmNPV could not replicate in Sf21 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The p143 gene of AcMNPV has helicase activity (McDougal & Guarino, 2001) and has been implicated as a host-range factor (Croizier et al, 1994;Kamita & Maeda, 1997). For example, although AcMNPV and BmNPV share high DNA sequence similarity, AcMNPV could not replicate in B. mori cells and BmNPV could not replicate in Sf21 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although AcMNPV and BmNPV share high DNA sequence similarity, AcMNPV could not replicate in B. mori cells and BmNPV could not replicate in Sf21 cells. The inability of AcMNPV to replicate in B. mori cells is due to the p143 gene of AcMNPV (Croizier et al, 1994;Kamita & Maeda, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified several viral genes that are involved in host range determination of Autographa californica multinucleocapsid NPV (AcMNPV) in insect cell systems (6,7,18,21,22,24,31). One of these genes, host range factor 1 (hrf-1) from the gypsy moth NPV, Lymantria dispar MNPV (LdMNPV), was identified as a factor that promoted AcMNPV replication in nonpermissive cell line Ld652Y (12), derived from L. dispar.…”
mentioning
confidence: 99%
“…Though DNA replication seemingly occurred as in the permissive Sf-21 cells, the defect in AcMNPV-BmN cells was shown to be caused by differences in the DNA helicase gene (p143) (Maeda et al, 1993). A few amino acid changes in AcMNV P143 were sufficient to overcome the defect in B. mori cells and larvae (Argaud et al, 1998;Croizier et al, 1994). The cytotoxicity and block in AcMNPV infection of B. mori cells are suggested to stem from aberrant DNA replication (reviewed in Thiem & Cheng, 2009;Rohrmann, 2011).…”
Section: Late Phase -Dna Replicationmentioning
confidence: 99%